Design of Falling Notification System using Falling Situation and Geofencing Service - Kwon, TaeWoo; Lee, Jong-Yong; Jung, Kye-Dong (International Journal of Engineering and Technology, 2018)
The existing falling notification system notifies only the occurrence of a falling and provides notification service. However, falling has different risk levels depending on the type and location of falling. Therefore, the falling notification system based on the falling situation is required. In this paper, we use accelerometer data of smartphone to recognize falling. In this system collects beacon and GPS sensor data to recognize falling location.This falling location data is used for geofencing service within a certain area when the falling occurs. The acceleration sensor data is converted into SVM(Signal Vector Magnitude) and used. When the falling occurs, it is converted not only into falling data, but also falling situation data using location information including pre-falling and post-falling data. However, when real-time processing of multiple data including sensor data, data overload, and connection speed delay problems arise. In this paper, we set up three layers of the system to minimize these problems.The three layers are composed of End Layer, Fog Layer, and Cloud Layer, respectively. Behavior data when no falling have occurred are stored in the temporary storage of the Fog Layer. If the falling does not occur for a certain period of time, the data stored in the temporary storage is deleted.When the falling occurs, the falling notification service is provided based on the falling situation. The notification service provides geofencing service in addition to SMS to the caregiver.Â Â